Co-Gasification of Crude Glycerol/Animal Fat Mixtures - Almeida, Ana F. (2021)
The aim of this work was to assess the technical viability of glycerol/fat co-gasification. The gasification performance was studied in a downflow fixed bed reactor using activated alumina particles as bed material and steam as oxidizing agent. The effect of gasification temperature, from 800 to 950 °C was studied with a feed mixture with 10% (w/w) of animal fat. The influence of fat incorporation on the feedstock in the overall gasification process was also performed, using 3% (w/w) and 5% (w/w) of fat in feed mixtures. Samples of dry gas from the gasifier were collected and analyzed by gas chromatography in order to determine the CO, CO2, CH4, and H2 content. The best results were obtained using the highest tested temperature, 950 °C, and using 3% (w/w) of animal fat in the feed mixture. The overall results revealed that the co-gasification of glycerol/animal fat mixtures seems to be a feasible technical option